Crowding-out or co-existence? the competitive position of EU members and China in global merchandise trade - Konstantins Benkovskis; Maria Silgoner; Katharina Steiner; Julia Wörz (European Central Bank (ECB), 2013)
In this paper, we analyse export competition between individual EU Member States and China in third-country goods markets. We find that competitive pressure from China is strongest for small and peripheral EU members, especially for the Southern periphery, Ireland and Central, Eastern and South-eastern European EU members. While we find no hard evidence for "cut-throat" competition between China and EU countries, we see an increasing tendency of smaller EU exporters leaving markets that are increasingly served by China. We base our findings on traditional market share analysis, the exploration of intensive versus extensive margin export growth and on a Dynamic Trade Link Analysis. The latter, a newly developed tool, identifies different types of competitive pressure at the detailed product-destination market level. We use UN Comtrade data at the highest level of disaggregation (6-digit HS) for 75 world exporters and importers over the period 2000-2011.
Keywords: F14; F15; O57; 330; China; competitiveness; European Union; extensive margin; sectoral market shares; trade links